Perkembangan Pernyataan Kehendak dan Keabsahannya dalam Smart Contract - Ariyanto Ariyanto (Law Policy Strategy Agency, Ministry of Law of The Republic of Indonesia, 2024)
The development of Smart Contract in this regard can be attributed to the stability of Indonesian law, where methods for executing contracts have become increasingly sophisticated. With the rapid growth of technological developments that use Smart Contracts and the urgency of the extent to which the current laws in Indonesia can support their development, the question arises of how Smart Contract work? When does the meeting of minds occur in a Smart Contract? And, how is the fulfillment of the principle of consensualisme in Smart Contract viewed from the perspective of Article 1320 of the Civil Code? The research method in this study was carried out using a qualitative normative method .The results of this study show, Smart Contract works by running without a third party and written on the Blockchain. Second, there is a meeting of minds in the Smart Contract, where both parties who intend to bind themselves in the Smart Contract send their cryptographic encryption to commit to each other in the Smart Contract, as proof that both have mutually agreed. Third, the principle of consensualism in Smart Contract from the perspective of Article 1320 of the Civil Code shows that agreement is an essential foundation for the validity of an agreement, ensuring that each party involved has agreed to the existing provisions.